(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2009)
This article discusses the relationship between the malay language and the identity of the individual and the race, particularly in relation to the Malays in Malaysia. The identity of an individual and a race is defoned from a philosophical perspective and cross-referenced with definitions by sociologist, historians and social scientists. Based on this, it is concluded that there are five elements that shape the identity of a race, that is, the same ancestry, language, culture, religion, and locale. Whilst there are elemental structures that undergrid an identity, there are factors that can cause an identity to change. This is discussed in light of a few hypotheses that the present article argues can generate change in the identity of a race. The article concludes that the change in the identity of an individual or a race happens when there is change in the language that is used. Makalah ini membincangkan tentang kaitan antara bahasa, khususnya bahasa Melayu dengan jati diri individu dan bangsa, khususnya Melayu di Malaysia. Definisi jati diri individu dan bangsa dikupas menggunakan kamus falsafah dan rujukan silang kepada beberapa definisi daripada ahli sosiologi, sejarah dan sains politik. Berdasarkan kupasan tersebut dirumuskan bahawa terdapat lima ciri yang membentuk jati diri bangsa, yakni leluhur, bahasa, kebudayaan, agama dan tempat tinggal yang sama. Namun begitu, di sebalik ciri yang membentuk jati diri terdapat juga mekanisme yang merangsang perubahannya. Makalah ini selanjutnya membincangkan beberapa hipotesis yang menjana perubahan jati diri sesebuah bangsa. Hipotesis yang dimaksudkan dikaitkan dengan bahasa dan sehubungan dengan hal ini makalah ini menyimpulkan bahawa perubahan jati diri individu atau bangsa berlaku apabila terdapat perubahan bahasa yang digunakan.